2021
DOI: 10.3390/atmos12080975
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality during New Year’s Eve: A Biomonitoring Study with Moss

Abstract: Mosses are one of the best bioindicators in the assessment of atmospheric aerosol pollution by heavy metals. Studies using mosses allow both short- and long-term air quality monitoring. The increasing contamination of the environment (including air) is causing a search for new, cheap and effective methods of monitoring its condition. Once such method is the use of mosses in active biomonitoring. The aim of the study was to assess the atmospheric aerosol pollution with selected heavy metals (Ni, Cu, Zn, Cd, Hg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Therefore, we have dispensed with such analyses (such as fluorescence and chlorophyll content testing) in this study. In our other work on biomonitoring with mosses carried out throughout, e.g., 3 months, we present the results of studies on, e.g., the vitality of mosses during their exposure (Świsłowski et al 2021e , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we have dispensed with such analyses (such as fluorescence and chlorophyll content testing) in this study. In our other work on biomonitoring with mosses carried out throughout, e.g., 3 months, we present the results of studies on, e.g., the vitality of mosses during their exposure (Świsłowski et al 2021e , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The monthly rainfall was 35.6 mm, 18.6 mm and 37.4 mm respectively, for the studied exposure months [87]. In previous studies, we have shown how important it is to consider the influence of environmental conditions on the accumulation of heavy metals by mosses [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in assessing air pollution caused by fine particulate matter containing HM is due to their relatively low concentrations. In such cases, large observation periods are required to obtain reliable results, which can be achieved through bioindication methods [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%